1988
DOI: 10.1111/j.1349-7006.1988.tb01528.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case‐Control Study of Gastric Cancer and Diet in Northern Kyushu, Japan

Abstract: A case‐control study of gastric cancer was done in a rural area of northern Kyushu, Japan, in relation to dietary habits especially focusing on the relationship with the consumption of broiled fish. The study was based upon 139 cases of newly diagnosed gastric cancer at a single institution, 2,574‐ hospital controls and 278 controls sampled randomly from the residents of the study area (with sex and year of birth matched). No association was observed between the consumption of broiled fish and gastric cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
123
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(131 citation statements)
references
References 15 publications
5
123
1
Order By: Relevance
“…The other factors are tobacco smoking (current, former, and currently not smoking), alcohol (current or currently not drinking), history of chronic gastric symptoms (yes or no), occupation (permanent or nonpermanent work), and coffee drinking (daily or occasionally). These factors control possible confounding factors (Haenszel et al, 1972;Hoey et al, 1981;Hisashige et al, 1983;Jeyaratnam et al, 1987;Kono et al, 1988;Yin et al, 1989;Hirayama, 1990;Kneller et al, 1990;Une et al, 1995;You et al, 1995;Galanis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The other factors are tobacco smoking (current, former, and currently not smoking), alcohol (current or currently not drinking), history of chronic gastric symptoms (yes or no), occupation (permanent or nonpermanent work), and coffee drinking (daily or occasionally). These factors control possible confounding factors (Haenszel et al, 1972;Hoey et al, 1981;Hisashige et al, 1983;Jeyaratnam et al, 1987;Kono et al, 1988;Yin et al, 1989;Hirayama, 1990;Kneller et al, 1990;Une et al, 1995;You et al, 1995;Galanis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
“…Kang and colleagues reported that 121.3 mg of EGCG was obtained from 5 g of dry green tea by extracting in 50 o C water (Kang et al, 1999). Also, Japanese epidemiologists reported that one cup of green tea infusion contained 100-200 mg of polyphenolic compounds (Kono et al, 1988). Therefore, the suggested daily dosage of polyphenols is 240 to 320 mg, equal to about 3 cups of green tea.…”
Section: Discussionmentioning
confidence: 99%